Transverse Myelitis in a Child with Chronic Recurrent Multifocal Osteomyelitis. (July 2022) - Cramer, Natan
A 16-year-old girl with a history of clavicular chronic recurrent multifocal osteomyelitis (CRMO) presented with fever, vomiting, urinary and bowel retention, thigh paresthesia, and back pain for 2 days. The patient had 2 separate viral illnesses within a month prior to presentation. Spine magnetic resonance imaging (MRI) displayed increased T2 hyperintensity of the central grey matter from C3 to the conus medullaris (Figure 1). Findings were consistent with longitudinally extensive transverse myelitis. Cerebrospinal fluid analysis revealed elevated protein (51; reference range: <48 mg/dL), IgG index (.74; reference range <.70), and glucose (99; reference range 40-75 mg/dL). There was pleocytosis of 22 white blood cells (88% lymphocytes and 12% monocytes) with negative AQP4 and MOG antibodies. COVID-19 spike protein was positive with a negative PCR and non-immunized status, suggesting prior infection. Four months later, a pelvic MRI revealed new evidence of CRMO.